1998
DOI: 10.1021/la9806505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanoscale Platinum Colloids by Microwave Dielectric Heating

Abstract: Polymer-stabilized platinum colloids with nearly uniform spherical shape were prepared by microwave dielectric heating. The average diameters of the as-prepared platinum colloids were 2−4 nm with a narrow size distribution in regard to the preparation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(101 citation statements)
references
References 21 publications
2
97
0
2
Order By: Relevance
“…After such high temperature annealing process, the specific capacitance of RuO 2 .xH 2 O would be significantly reduced. A new method must be developed for making Pt or PtRu on RuO 2 .xH 2 O at low temperature such as <150 o C. It was reported that the microwave was applied to the boiling temperature at which the metal nanoparticles are formed [21], [22]. The advantage of this method is that the solution will rapidly heat up and cool down (less than 1 minute) to accelerate the reduction of the metal precursor ions and the nucleation of the metal particle in order to guarantee the particle size on the order of nm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…After such high temperature annealing process, the specific capacitance of RuO 2 .xH 2 O would be significantly reduced. A new method must be developed for making Pt or PtRu on RuO 2 .xH 2 O at low temperature such as <150 o C. It was reported that the microwave was applied to the boiling temperature at which the metal nanoparticles are formed [21], [22]. The advantage of this method is that the solution will rapidly heat up and cool down (less than 1 minute) to accelerate the reduction of the metal precursor ions and the nucleation of the metal particle in order to guarantee the particle size on the order of nm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…On the other hand, from the viewpoint of nanofabrication, it has been demonstrated that the size of the produced nanostructures in a colloid system could be decreased by introducing polymeric surfactant molecules to the synthesis system [30,[34][35][36][37][38][39][40]. These polymeric surfactant molecules are suggested to work as stabilizer or capping agents to hamper the further growth of the formed nanospecies, resulting in smaller nanostructures [30,[34][35][36][37][38][39][40]. For example, it has recently been reported that the size of the Ag/AgCl nanoparticles could be decreased with the assistance of polymeric surfactant molecules, poly(vinyl pyrrolidone) [40].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
“…For example, it has recently been reported that the size of the Ag/AgCl nanoparticles could be decreased with the assistance of polymeric surfactant molecules, poly(vinyl pyrrolidone) [40]. On the basis of these well-documented understandings [30,[32][33][34][35][36][37][38][39][40] and accompanied by our experimental facts, we suggest that in our system the GO nanosheet, an unconventional amphiphilic polymer, might work as capping agent or stabilizer to hamper the further growth of the Ag/Ag 3 PO 4 nanoparticles, resulting in smaller size of the formed nanostructures. Similar results have been reported in other systems [28][29][30].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
“…[37][38][39] This review deals with the effects of US and MW on the catalyst preparation as well as reduction. As far as catalyst preparation is concerned, the advantages of sonication and MW irradiation, such as reductions in preparation time and excellent catalytic performance, are emphasized.…”
Section: Introductionmentioning
confidence: 99%